STRATEGI GURU PAI DALAM MEMBENTUK KARAKTER RELIGIUS SISWA MELALUI PEMBELAJARAN JARAK JAUH PADA MASA PANDEMI - Sabar Sahiroh; Moh. Sakir; Lutfan Muntaqo (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2022)
This thesis examines the strategy of Islamic religious education teachers in shaping the religious character of students through distance learning during the fifth grade pandemic at SD Muhammadiyah Bilingual Fullday Al Adzkiya Wonosobo. The purpose of this research is to find out the strategies of Islamic Religion Teachers used in learning during the COVID-19 pandemic in shaping the religious character of fifth grade students through distance learning so that they can run optimally, effectively, efficiently and can take place well. This study uses a descriptive qualitative approach. The research subject is a teacher of Islamic religious education class V, the types of data used are primary data and secondary data. Primary data sources consist of school principals, Islamic religious education teachers, classroom teachers and students. Secondary data sources consist of school documentation data, teacher data, student data, facilities and infrastructure data. The main research instrument is the researcher himself then developed with a guide observation, interviews, and documentation. The technique of data processing and data analysis went through three stages, namely, data reduction, data presentation and drawing conclusions. The results showed that: (1) the condition of the religious character of fifth graders was good, namely with character values ​​ranging from religious aspects, cleanliness and tidiness, honesty, discipline and responsibility, besides that there was Life Skills Education which included: (a) Practical worship, (b) Read and write the Qur'an, (c) Tahfidz. (2) PAI Learning Strategies: (a) make a Learning Implementation Plan (RPP) in accordance with the distance learning syllabus during the covid 19 pandemic. The use of learning methods centered on online methods, multimedia-based media in the form of powerpoint modules and communication media for whatsapp group platforms and google classroom. (b) strategy implementation: pre-learning activities are carried out in the form of question and answer interactions. Interaction during learning, in the form of information exchange or reciprocal relationships between teachers and students. (c) Evaluation and assessment: the form of evaluation is in the form of multiple choice tests via google form and assessment in the form of giving assignments to be done in the form of a portfolio. (3) Obstacles faced by Islamic Religious Education Teachers in shaping the religious character of fifth grade students, namely: Family environment, social factors and digital technology factorsThe solution: Cooperating with parents and providing motivation to students.